Oral reading fluency: learning English as a second language in Malaysia - Gan, Hui Hong (Universiti Malaysia Sarawak (UNIMAS), 2015)
Oral reading fluency (ORF) and comprehension are interrelated in early reading skills. This project studied the ORF and comprehension among Year 2 English as a Second Language (ESL) learners (N = 27) in a Malaysian National Type (Chinese) School (S. J. K. (C)), Kuching, Sarawak. Two ORF passages and one comprehension tests were assessed individually. The entire ORF procedure was audio recorded. The ORF-One Minute (ORF-60) and ORF-Full Passage (ORF-FP) were computed using the formula in terms of words correct per minute (WCPM). The results were compared to the benchmark goal in the United States (U.S.). There was a gap between the learners‟ achievement in both countries The reading problems were identified, classified, analysed, and elaborated. Mispronunciations top the participants‟ oral reading problems. Negative transfer of other language was one of the factors of the problems. The findings of this project illuminate the importance of providing early remedial help for young participants in language and literacy.